2007
DOI: 10.1093/eurheartj/ehm441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triangle ventricular pacing on haemodynamics and dyssynchrony in patients with advanced heart failure: a comparison study with conventional bi-ventricular pacing therapy

Abstract: The acute beneficial effects of Tri-V on LV function and dyssynchrony were greater than those of Bi-V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…For instance, in the BiV + intrinsic programming, the ventricles can be activated from 3 sites: 2 ventricular pacing sites localized in the left and right ventricles and the AVN (the sinus activation through AVN). Leclercq, et al 19) and Yoshida, et al 20) have reported that multi-site pacing demonstrates superior reverse remodeling of the left ventricle, together with increased LV dp/dt and cardiac output. Consistent with our findings in the present study, Vatasescu, et al showed a shorter LV activation time and a better CRT responder rate during bi-ventricular pacing with fusion, when compared to the results with conventional CRT.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the BiV + intrinsic programming, the ventricles can be activated from 3 sites: 2 ventricular pacing sites localized in the left and right ventricles and the AVN (the sinus activation through AVN). Leclercq, et al 19) and Yoshida, et al 20) have reported that multi-site pacing demonstrates superior reverse remodeling of the left ventricle, together with increased LV dp/dt and cardiac output. Consistent with our findings in the present study, Vatasescu, et al showed a shorter LV activation time and a better CRT responder rate during bi-ventricular pacing with fusion, when compared to the results with conventional CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show that dual site RV pacing associated with LV pacing produced superior LV resynchronization and systolic performance when compared with conventional Biv pacing 30 and that reverse remodelling with dual site LV pacing associated with RV pacing is superior to conventional Biv pacing. 31 These data strengthen the idea of the superiority of three activation fronts during CRT (a situation reproduced during CRT with fusion).…”
Section: Discussionmentioning
confidence: 99%
“…Let-7i, miR-132, miR-199a) of many host cellular miRNAs [67]. The modulation of these host miRNAs has an effect on the expression of cellular proteins such as p300, NF-kB, and BRM, to name a few, which are all recruited by Tax and play a key role in activating HTLV-1 gene transcription [5,[30][31][32][33][34][35][36][38][39][40][44][45]56,60,[68][69][70][71]. To better define the functional significance of Drosha downregulation by Tax, we transfected 293T cells with pACH.Tax (5 mg) and 24 hours later added back pGFP-Drosha (10 mg).…”
Section: Suppression Of Cellular Mirnas By Htlv-1 Can Be Rescued By Omentioning
confidence: 99%